Kaposi Varicelliform Eruption in a Chronic Kidney Disease Individual Under Tacrolimus: A Case Report - Seema Sitaula; Suraj Shrestha; Elisha Poddar; Rabin Gosain (Hindawi Limited, 2024)
Conclusion: KVE is a serious condition that may have fatal outcomes. Early diagnosis and appropriate treatment of patients at risk for viral complications are very important medical considerations.